2007
DOI: 10.1016/j.brainres.2006.12.083
|View full text |Cite
|
Sign up to set email alerts
|

Selective septohippocampal – but not forebrain amygdalar – cholinergic dysfunction in diencephalic amnesia

Abstract: A rodent model of diencephalic amnesia, pyrithiamine-induced thiamine deficiency (PTD), was used to investigate diencephalic-limbic interactions. In-vivo acetylcholine (ACh) efflux, a marker of memory-related activation, was measured in the hippocampus and the amygdala of PTD-treated and pair-fed (PF) control rats while they were tested on a spontaneous alternation task. During behavioral testing, all animals displayed increases in ACh efflux in both the hippocampus and amygdala. However, during spontaneous al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 58 publications
(129 reference statements)
3
51
0
Order By: Relevance
“…Stereological estimates of the total number of ChAT+ neurons within the of MS/DB replicated previous findings that PTD treatment reduces (≈25%) the number of ChAT+ neurons that reside within the MS/DB (Roland and Savage, 2009; Savage et al, 2007), compared to PF control (F[1, 56]=18.42, p<0.01). A novel finding was that exercise (F[1, 56]=4.64, p<0.05) led to an increase in the number of cells that expressed the ChAT+ phenotype in the MS/DB (Figure 7, Panels A–B).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Stereological estimates of the total number of ChAT+ neurons within the of MS/DB replicated previous findings that PTD treatment reduces (≈25%) the number of ChAT+ neurons that reside within the MS/DB (Roland and Savage, 2009; Savage et al, 2007), compared to PF control (F[1, 56]=18.42, p<0.01). A novel finding was that exercise (F[1, 56]=4.64, p<0.05) led to an increase in the number of cells that expressed the ChAT+ phenotype in the MS/DB (Figure 7, Panels A–B).…”
Section: Resultssupporting
confidence: 79%
“…The parameters employed were based on previously published studies (Li et al, 2008; Roland and Savage, 2009; Savage et al, 2007; Yoder and Pang, 2005). An experimenter blind to both the Treatment, Exercise and Time point conditions performed cell counts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the pyrithiamine-induced thiamine deficiency (PTD) animal model of WKS, our laboratory has demonstrated a functional impairment of the hippocampus as evidenced by blunted hippocampal acetylcholine (ACh) efflux when rats were tested on spontaneous alternation (Savage et al, 2003;Savage, Roland, & Klintsova, 2007) and nonmatching-toposition tasks . The observed deficits in behavior and hippocampal ACh efflux could be the result of a number of several factors.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological studies have demonstrated that LS-hippocampus-hypothalamus-midbrain consisted limbic midbrain loop is an important pathway to hippocampus and act on regulating excitability of hippocampal neurons (Kendig et al, 1991;Franks and Lieb, 1994), and septohippocampal pathway has connection with anesthesia and amnesia (Savage et al, 2007). In our study, we observed that Fos expression was detected in the LS, CA1, DG, DM, Cg1, Cg2, PAG, and PV under incomplete anesthesia induced by sevoflurane, and more regions were detected under complete anesthesia.…”
Section: Discussionmentioning
confidence: 99%